2023
DOI: 10.7759/cureus.37238
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Coronary Artery Bypass Grafting Combined With Mitral Valve Repair Versus Coronary Artery Bypass Grafting Alone in Patients With Moderate Ischemic Mitral Regurgitation: A Meta-Analysis

Abstract: The aim of this meta-analysis was to compare clinical outcomes between those who underwent coronary artery bypass grafting (CABG) alone and CABG with mitral valve repair (MVR) in patients with moderate ischemic mitral regurgitation. The present study was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Two authors performed a comprehensive search of international databases, including PubMed, EMBASE, and the Cochrane Library, for relevant studies pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…Several meta-analyses 39 43 have assessed the therapeutic effects of MVR + CABG for patients with moderate IMR compared with CABG alone. Similar to our study, they found that MVR + CABG did not increase the risk of operative mortality but did not provide long-term survival benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Several meta-analyses 39 43 have assessed the therapeutic effects of MVR + CABG for patients with moderate IMR compared with CABG alone. Similar to our study, they found that MVR + CABG did not increase the risk of operative mortality but did not provide long-term survival benefits.…”
Section: Discussionmentioning
confidence: 99%
“…The organ most frequently involved in the overlap between SLE and AAV is the kidney, although any organ or system can be involved [9,10]. Other common clinical manifestations include articular and cutaneous features, but hematologic, pulmonary, cardiac, and ENT manifestations can also be present [11][12][13][14][15]. Neurologic manifestations are rare in SLE-AAV overlap syndrome and have only been previously documented as cerebral ischemia or infarction [16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%